Production of Natural Dye from Butterfly Pea Flower (Clitoria Ternatea T.) Extract Using Citric Acid Solvent from Bilimbi (Averrhoa bilimbi) - Putri Faradilla; Annura Nazila Mumtaz; Nabilah Azzahra; Ramot Andre Samuel Purba; Santriyani Zega; Talitha Zahira; Dwi Sapri Ramadhan (Universitas Negeri Medan, 2025)
Natural dyes extracted from butterfly pea flowers (Clitoria ternatea L.) hold significant potential as alternatives to synthetic dyes in the food and textile industries. This study aims to evaluate the effectiveness of citric acid isolated from bilimbi (Averrhoa bilimbi L.) as a solvent for extracting anthocyanin pigments from butterfly pea flowers. Ultrasonic extraction was conducted using different solvents (citric acid and ethanol) and varying extraction durations. The results showed that the extract yield ranged from 2.6% to 5.5%, with an average of 3.99%. Ethanol produced a higher yield than citric acid; however, citric acid significantly reduced the extract’s pH to a range of 1–6, potentially enhancing anthocyanin pigment stability. Additionally, extraction time positively influenced yield up to an optimal point, after which degradation of active compounds led to a decline. These findings suggest that bilimbi-derived citric acid has potential as an eco-friendly solvent for natural dye production, though further optimization is needed to enhance extraction efficiency and color stability.